Retrospective‐prospective study of safety and efficacy of sofosbuvir‐based direct‐acting antivirals in HIV/HCV‐coinfected participants with decompensated liver disease pre– or post–liver transplant. Issue 5 (23rd December 2020) - Peters, Marion G.; Kottilil, Shyam; Terrault, Norah; Amara, Dominic; Husson, Jennifer; Huprikar, Shirish; Florman, Sander; Sulkowski, Mark S.; Durand, Christine M.; Luetkemeyer, Anne F.; Rogers, Rodney; Grab, Joshua; et al.
Abstract : Direct‐acting antiviral (DAA) therapy has transformed the management of human immunodeficiency virus (HIV) and hepatitis C (HCV) coinfected patients with advanced liver disease. STOP‐Coinfection was a multicenter prospective and retrospective, open‐label study using sofosbuvir‐based DAA therapy to treat HIV/HCV‐coinfected participants pre– or post–liver transplant (LT). Sixty‐eight participants with end‐stage liver disease (Child‐Turcotte‐Pugh score ≥7 and Model for End‐Stage Liver Disease score 6–29) were enrolled, 26 had hepatocellular carcinoma. Forty‐two participants were treated pre–LT and 26 post–LT. All participants completed therapy without need for dose reduction or transfusion; eight required two or more courses of therapy. Ninety‐three percent achieved a sustained virologic response and DAA therapy was well tolerated. Despite HCV cure, 12 end‐stage liver disease participants required subsequent LT, 7 for decompensated liver disease. Thirteen participants died, 10 with decompensated liver disease pre–LT and three post–LT. Overall, transplant free survival was 42.8% at 4 years and post–LT survival was 87.9% at 5 years. We conclude that sofosbuvir‐based DAA therapy is safe and highly effective in HCV‐HIV patients with decompensated liver disease and post–LT, with post–LT survival rates comparable to other indications. This removes one of the last barriers to liver transplantation in this challenging cohort of recipients. Abstract : This study finds that sofosbuvir‐based direct‐acting antiviral therapy is safe and highly effective in HCV/HIV coinfected patients with decompensated liver disease and is associated with post–liver transplant survival rates comparable to other indications.